2015
DOI: 10.1097/mao.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Age and Radiographic Incidence of Superior Semicircular Canal Dehiscence in Pediatric Patients

Abstract: Radiographic SSCD, although uncommon, appears to be more prevalent in younger children, especially infants younger than 12 months. This suggests that the SSC may develop more bony covering with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…Nevertheless, hearing loss was the most common indication for CT scans in our analysis, as in previous studies. 11,14 Similarly, the child in our illustrative case was diagnosed with SSCD during routine investigation of hearing loss. Some studies specifically evaluated temporal bone CT scans to determine the radiological prevalence of SSCD in pediatric patients but did not report the indication for imaging.…”
Section: Managementmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, hearing loss was the most common indication for CT scans in our analysis, as in previous studies. 11,14 Similarly, the child in our illustrative case was diagnosed with SSCD during routine investigation of hearing loss. Some studies specifically evaluated temporal bone CT scans to determine the radiological prevalence of SSCD in pediatric patients but did not report the indication for imaging.…”
Section: Managementmentioning
confidence: 79%
“…To address these deficiencies, we provide a quantitative summary of published cases of pediatric SSCD and highlight the divergent features of the clinical presentation and management. A total of 14 articles 4,10,11,14,15,18,20,22,23,29,31,32,[34][35][36] comprising 122 cases were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Hagiwara et al (9) reviewed CT scans of 34 children younger than 2 years and found radiographic dehiscence in 13.8% and 20% of temporal bones for the superior and posterior canals, numbers comparable to those seen in the same age distribution in our study. Jackson et al (10) found radiographic superior canal dehiscence in 7.1% of temporal bones less than 1 year of age using CT slice thickness of 1 mm or less. It is unclear whether this study's data represent the true prevalence, however, given prior studies demonstrating improved predictive value of CT using a collimation of 0.625 mm or less (11).…”
Section: Prevalence Of Dehiscencementioning
confidence: 99%
“…A first causative factor is thought to be a temporal bone thickening disorder, more probably a combination of a defective development in younger age and/or an age-related osteopenia in the middle age. Indeed, the radiological prevalence of bone defects at the level of the superior canal is high in children (37), decreases in young age (38) and worsens in middle age (39).The second "hit" is often an incidental factor, such as a minor skull trauma or a wrong pressuring maneuver that can precipitate a silent canal dehiscence/thinning into a symptomatic entity. The debut of the SCDS in concomitance with minor head traumas or other incidental factors is reported in approximately half of the patients affected by SCDS (40).…”
Section: The Superior Canal Dehiscence Syndrome (Scds)mentioning
confidence: 99%